Persons with Reconstructed ACL Exhibit Altered Knee Mechanics during High-Speed Maneuvers - Lee, S.-P.; Chow, J. W.; Tillman, M. D. (International Journal of Sports Medicine, 2014)
Anterior cruciate ligament (ACL) injury is a sports trauma that causes long-term disability. The function of the knee during dynamic activities can be severely limited even after successful surgical reconstruction. This study examined the effects of approach velocity during side-step cutting on knee joint mechanics in persons with reconstructed ACL (ACLR). 22 participants (11 with unilateral ACLR, 11 matched-controls) participated. Knee joint mechanics were tested in 3 approach conditions: counter-movement, one-step, and running. Dependent variables, including peak knee flexion, extension, valgus, varus, internal rotation, external rotation angles and corresponding peak joint moments, were assessed during the stance phase of cutting. Two 2×3 (“group” by “approach condition”) mixed MANOVA tests were used to examine the effects of ACLR and approach velocity on knee mechanics. ACLR participants exhibited higher knee internal rotator moment (0.22 vs. 0.13 Nm/kg, p=0.003). Inter-group comparisons revealed that the ACLR participants exhibited significantly higher abductor and internal rotator moments only in the running condition (1.86 vs. 1.16 Nm/kg, p=0.018; 0.28 vs. 0.17 Nm/kg, p=0.010, respectively). Our findings suggested that patients with ACLR may be at increased risk of re-injury when participating in high-demand physical activities. Task demand should be considered when prescribing progressive therapeutic interventions to ACLR patients.
Keywords: anterior cruciate ligament; cutting; knee; biomechanics; injury